PAuthKey: A Pervasive Authentication Protocol and Key Establishment Scheme for Wireless Sensor Networks in Distributed IoT Applications - Pawani Porambage; Corinna Schmitt; Pardeep Kumar; Andrei Gurtov; Mika Ylianttila (International Journal of Distributed Sensor Networks)
Wireless sensor Networks (WSNs) deployed in distributed Internet of Things (IoT) applications should be integrated into the Internet. According to the distributed architecture, sensor nodes measure data, process, exchange information, and perform collaboratively with other sensor nodes and end-users, which can be internal or external to the network. In order to maintain the trustworthy connectivity and the accessibility of distributed IoT, it is important to establish secure links for end-to-end communication with a strong pervasive authentication mechanism. However, due to the resource constraints and heterogeneous characteristics of the devices, traditional authentication and key management schemes are not effective for such applications. This paper proposes a pervasive lightweight authentication and keying mechanism for WSNs in distributed IoT applications, in which the sensor nodes can establish secured links with peer sensor nodes and end-users. The established authentication scheme PAuthKey is based on implicit certificates and it provides application level end-to-end security. A comprehensive description for the scenario based behavior of the protocol is presented. With the performance evaluation and the security analysis, it is justified that the proposed scheme is viable to deploy in the resource constrained WSNs.